The Efficacy of a Program Promoting Rice Self-Sufficiency in Ghana during a Period of Neoliberalism - Glenna, L.; Ader, D.; Bauchspies, Wenda; Traoré, A.; Agboh-Noameshie, A.R. (Wiley, 2012)
The number of the world's food insecure rose at the end of the first decade of the twenty-first century. Despite these negative developments, however, a 2010 United Nations report argues that food security could be improved if development efforts are supported by government programs that target smallholder farmers. This report is significant because it challenges the neoliberal perspective, which tends to promote a private-enterprise market system and favor large-scale producers. These competing visions for agricultural development frame our evaluation of the impact of the Africa Rice Center's (AfricaRice) efforts to promote new rice varieties among smallholder farmers to narrow the rice consumption-production gap in Ghana. We begin by distinguishing the outreach efforts to help farmers increase production and the political-economic conditions that limit the longevity of that outreach effort. We reviewed program documents revealing expenditures and yields among the smallholder farmers, and we conducted intensive interviews with the farmers. Although we find that the program succeeded in mobilizing farmers to increase rice production, we question the sustainability of the program's impact because state funding for the program has ended